Enhance Chinese students’ initial motivation through communicative activities based on Cefr and Elp purposes. Case study at the University of Nottingham Ningbo China - Gilardi, Filippo (Elsevier, 2012)
This article describes how French language tutors at The University of Nottingham Ningbo China have used different tools to shape the French language curriculum to improve communicative language competences and motivation. The French curriculum used the Common European Framework of Reference for Languages as its organizing principle to promote students’ self-study development and make them aware of the key objectives of the European Language Portfolio.